Pola Asuh Nenek dan Implikasinya terhadap Perilaku Sosial Emosional Anak di Desa Tenembak Lang-Lang Kabupaten Aceh Tenggara - Zuraini Mahyiddin; Melisa Purnama; Sitti Muliya Rizka (Journal on Education, 2023)
This study aims to explain grandmother's parenting and its implications for children's social-emotional behavior in Tenembak Lang-Lang Village, Southeast Aceh Regency. Factors that cause children to be cared for by grandmothers are parents who work outside, parents are widows or widowers due to death and divorce. This study uses a qualitative approach with the research subject of 5 grandmothers. Data were collected by means of observation, interviews and documentation. The results showed that there were two kinds of parenting styles used by grandmothers in Tenembak Lang-Lang Village, namely democratic and permissive parenting. The grandmother who uses permissive parenting is R1, R3, R4, R5 and democratic parenting is R2. Children's social-emotional behavior in grandmother's care tends to be independent and irresponsible, children also seem spoiled, unable to rely on and regulate themselves. The parenting style applied by the grandmother in the village of Tenembak Lang-lang is one of the factors that influence the social emotional behavior of children. This research is expected to provide good benefits for readers, as well as become a relevant reference for other research related to parenting patterns in a family.